2020
DOI: 10.11113/jt.v82.14493
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Micronucleus Frequency and Respiratory Health Symptoms Among Traffic Policemen Exposed to Btex and PM2.5 in Klang Valley, Malaysia

Abstract: Volatile organic compounds such as benzene, toluene, ethylbenzene, xylene (BTEX), and particulate matter (PM) with a diameter of less than 2.5 microns (PM2.5) are often associated with traffic-related air pollution (TRAP) and harm the health of the community. This study aimed to evaluate the personal air pollutant exposure, micronucleus (MN) frequency, and respiratory health symptoms among 160 traffic policemen and 149 office workers in Klang Valley. Personal exposure concentrations for BTEX and PM2.5 among tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A fact that could be considered a limitation of the present study was other toxic pollutants emitted from motor vehicles were not investigated in this study. DNA damage could also be induced by numerous environmental pollutants besides PAHs (i.e., Benzene and 1,3-butadiene) [ 76 , 77 ]. Future research should be conducted on quantification of other carcinogenic pollutants such as toxic gases (benzene, toluene, ethylbenzene, xylenes) to evaluate comprehensively the combine effects of exposure to urban air pollutants on genotoxic effects in children.…”
Section: Resultsmentioning
confidence: 99%
“…A fact that could be considered a limitation of the present study was other toxic pollutants emitted from motor vehicles were not investigated in this study. DNA damage could also be induced by numerous environmental pollutants besides PAHs (i.e., Benzene and 1,3-butadiene) [ 76 , 77 ]. Future research should be conducted on quantification of other carcinogenic pollutants such as toxic gases (benzene, toluene, ethylbenzene, xylenes) to evaluate comprehensively the combine effects of exposure to urban air pollutants on genotoxic effects in children.…”
Section: Resultsmentioning
confidence: 99%
“…Malaysian traffic police have a duty to regulate, control, and divert traffic and the majority of them work until their retirement. This means they are continuously exposed to toxic air pollutants while working in the middle of roads and are at risk of possible adverse health effects (Muhammad et al, 2012(Muhammad et al, , 2014Awang et al, 2018Awang et al, , 2019Awang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Although TVOC typically records higher concentration indoors, the findings in this study did not show similar outcomes because there was a limited source of TVOC, such as paints and floorings. The detected TVOC concentration was most likely contributed by traffic emissions outdoors, such as benzene, ethylbenzene, ethylbenzene, and xylene, as previous local studies had reported [49,53]. These four aro-matics compounds are more commonly known as BTEX, resulting from traffic exhaust emissions and indoor sources.…”
Section: Concentrations Of Air Pollutants In Schoolsmentioning
confidence: 76%